Comparing The Acceleration Due to Gravity using Traditional Method Versus Tracker Video Analysis: Experiments in A Simple Pendulum - Pacala, Frank Angelo; Mendaño, Rezy (Universitas Negeri Semarang, 2025)
This study used a simple pendulum to compare the accuracy and precision of the traditional method and Tracker video analysis in determining the acceleration due to gravity (g). The experiment involved two groups of participants: science teachers in the Philippines, who used the traditional method, and high school students in Uzbekistan, who employed video analysis. Both groups conducted multiple trials by measuring the period of the swinging pendulum. Data were collected by manually recording the pendulum’s motion with a stopwatch or through video analysis software, and the resulting periods were used to calculate g. The data were analyzed by comparing the measured values of g from both methods and assessing the precision and accuracy of each. The results indicated that the traditional method provided more accurate g measurements than the video analysis method, though both methods yielded results close to the accepted average value of 9.81 ms−2. The study suggests that both methods are feasible, but user experience and familiarity with the tools significantly impact the results.